A new redundancy resolution for underwater vehicle–manipulator system considering payload. (26th September 2017) - Wang, Yaoyao; Jiang, Surong; Yan, Fei; Gu, Linyi; Chen, Bai
For the motion coordination problem between the underwater vehicle and manipulator of the underwater vehicle–manipulator system, a new redundancy resolution method is proposed and investigated. The proposed method mainly has two parts: a fuzzy logic part and a multitasks weighted gradient projection method part. The fuzzy logic part is used to decide the weight factors of the motion distribute matrix and the priorities of all the secondary objectives, while the multitasks weighted gradient projection method part is used to handle the secondary objectives with the weight factors and priorities decided by the fuzzy logic part. Moreover, a new secondary objective is proposed to optimize underwater vehicle–manipulator system's attitude, which takes the payload into consideration. Finally, the effectiveness of the proposed redundancy resolution is verified through some comparative simulations.